2023
DOI: 10.1021/acsomega.2c06916
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antineuroinflammatory Mechanisms of Kaempferol-3-O-β-d-Glucuronate on Lipopolysaccharide-Stimulated BV2 Microglial Cells through the Nrf2/HO-1 Signaling Cascade and MAPK/NF-κB Pathway

Abstract: Aglycone-and glycoside-derived forms of flavonoids exist broadly in plants and foods such as fruits, vegetables, and peanuts. However, most studies focus on the bioavailability of flavonoid aglycone rather than its glycosylated form. Kaempferol-3-O-β-D-glucuronate (K3G) is a natural flavonoid glycoside obtained from various plants that have several biological activities, including antioxidant and anti-inflammatory effects. However, the molecular mechanism related to the antioxidant and antineuroinflammatory ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Importantly, the impacts of kaempferol have not yet been completely identified on the reproductive system. Current results revealed that the administration of kaempferol following exposure to lead caused elevation in the levels of CAT, GPx, and SOD, whereas MDA and NO were reduced relative to their levels in rats treated with vitamin E and/or lead only; this may be attributed to the antioxidant ability of kaempferol to suppress the activities of pro-oxidant enzymes such as xanthine oxidase that responsible for generating ROS ( Lim et al , 2023 ). Kaempferol, like other flavonoids, can chelate with cuprous or ferrous ions in Fenton’s reaction, ultimately leading to prevent lipid peroxidation of cytomembrane, as well as; kaempferol increases the expression and activity of CAT, GPx, and SOD, as found by ( Lim et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the impacts of kaempferol have not yet been completely identified on the reproductive system. Current results revealed that the administration of kaempferol following exposure to lead caused elevation in the levels of CAT, GPx, and SOD, whereas MDA and NO were reduced relative to their levels in rats treated with vitamin E and/or lead only; this may be attributed to the antioxidant ability of kaempferol to suppress the activities of pro-oxidant enzymes such as xanthine oxidase that responsible for generating ROS ( Lim et al , 2023 ). Kaempferol, like other flavonoids, can chelate with cuprous or ferrous ions in Fenton’s reaction, ultimately leading to prevent lipid peroxidation of cytomembrane, as well as; kaempferol increases the expression and activity of CAT, GPx, and SOD, as found by ( Lim et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current results revealed that the administration of kaempferol following exposure to lead caused elevation in the levels of CAT, GPx, and SOD, whereas MDA and NO were reduced relative to their levels in rats treated with vitamin E and/or lead only; this may be attributed to the antioxidant ability of kaempferol to suppress the activities of pro-oxidant enzymes such as xanthine oxidase that responsible for generating ROS ( Lim et al , 2023 ). Kaempferol, like other flavonoids, can chelate with cuprous or ferrous ions in Fenton’s reaction, ultimately leading to prevent lipid peroxidation of cytomembrane, as well as; kaempferol increases the expression and activity of CAT, GPx, and SOD, as found by ( Lim et al , 2023 ). Furthermore, kaempferol possesses a double bond at C3-C2 and hydroxyl groups at C5, C3, and C4, and an oxo group at C4 which might explain its powerful antioxidant properties ( Imran et al , 2019 ); the current results consistent with ( Albrakati et al , 2021 ) who concluded that kaempferol can suppress lipid peroxidation and NO production with increase generation of antioxidants in neurotoxic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Kaempeferitin a derivative of KPF delayed the onset of myoclonic seizures, generalized seizures, and decreased mortality in Swiss Webster mice and Wistar rats (González‐Trujano et al, 2017). Further, the synthetic KPF analogs have been reported to ameliorate the phosphorylation of NF‐kB, reduction in COX‐2, iNOS, and promote the AMPK/NRF2/HO‐1 pathway in epilepsy conditions (Lim et al, 2023; Velagapudi et al, 2019). Altogether, these findings indicate that KPF could be a promising antiepileptic agent.…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 99%
“…Brain inflammation has been shown to play a causal role in the neurodegeneration in ischemia-reperfusion injury ( Section 2 ) and in NPA intoxication ( Section 3 ), and recent reviews have highlighted the molecular mechanisms of action of flavonoids as anti-inflammatory molecules, see, for example [ 199 , 200 ]. The anti-inflammatory actions of kaempferol are well recognized [ 201 , 202 ], and it is to be noted that recently it has been shown with lipopolysaccharide-stimulated BV2 microglial cells that its derived glucuronate metabolite also displays cellular antioxidant and anti-neuroinflammatory activity [ 203 ]. Kaempferol administration has been shown to inhibit astrogliosis and/or microglia activation in the brain of animal models of MCAO [ 41 , 76 , 78 , 79 ] and of NPA-induced neurological dysfunction [ 43 , 48 , 139 , 140 , 141 ].…”
Section: Molecular and Cellular Mechanisms That Contribute To Kaempfe...mentioning
confidence: 99%